A concretização do princípio da igualdade em matéria tributária por meio de sentenças aditivas - Zaranza Filho, José Evandro Lacerda (2009)
This work aims to study the additive decisions, a type of juridical interpretation developed in foreign legal systems and which are known in Italy as adittive sentences. Thefore, this dissertation is based on theorical studies developed around the subject in Italy and Brazil. Considering the fact that the fundamental rights face a problem of implementation, being decreased its normative force when there are legislative partial omissions lacking constitutional justification creating privileges to certain individuals or social/economical groups over others, the method of additive interpretation according to the Constitution can be used in order to realize the principle of equality. In tax matters the subject is even more relevant in the way that it represents an important role in the economy. Partial legislative omissions can generate inequalities, favoring certain taxpayers in relation to others in similar legal situation. In these cases the privilege may have a negative impact on economic order restricting values related to the basis of market competition. On those occasions, Brazilian Judges and Courts must exercise their constitutional jurisdiction in order to expand the effects of the legislative omissions, based on the principle of equality by extending the standard to equal tax situations in order to maintain neutrality in taxation